Mind the Gap: The Effect of Keyboard Key Gap and Pitch on Typing Speed, Accuracy, and Usability, Part 3. (November 2015) - Madison, Heather; Pereira, Anna; Korshøj, Mette; Taylor, Laura; Barr, Alan; Rempel, David
Objective: The aim of this study was to evaluate the effects of key gap (distance between edges of keys) on computer keyboards on typing speed, percentage error, preference, and usability. Background: In Parts 1 and 2 of this series, a small key pitch (center-to-center distance between keys) was found to reduce productivity and usability, but the findings were confounded by gap. In this study, key gap was varied while holding key pitch constant. Method: Participants ( N = 25) typed on six keyboards, which differed in gap between keys (1, 3, or 5 mm) and pitch (16 or 17 mm; distance between centers of keys), while typing speed, accuracy, usability, and preference were measured. Results: There was no statistical interaction between gap and pitch. Accuracy was better for keyboards with a gap of 5 mm compared to a 1-mm gap ( p = .04). Net typing speed ( p = .02), accuracy ( p = .002), and most usability measures were better for keyboards with a pitch of 17 mm compared to a 16-mm pitch. Conclusions: The study findings support keyboard designs with a gap between keys of 5 mm over 1 mm and a key pitch of 17 mm over 16 mm. Applications: These findings may influence keyboard standards and design, especially the design of small keyboards used with portable devices, such as tablets and laptops.